TLR4-dependent neuroinflammation mediates LPS-driven food-reward alterations during high-fat exposure - Sabrina J. P. Huwart; Clémence Fayt; Giuseppe Gangarossa; Serge Luquet; Patrice D. Cani; Amandine Everard (Journal of Neuroinflammation)
Abstract Background Obesity has become a global pandemic, marked by significant shifts in both the homeostatic and hedonic/reward aspects of food consumption. While the precise causes are still under investigation, recent studies have identified the role of gut microbes in dysregulating the reward system within the context of obesity. Unravelling these gut–brain connections is crucial for developing effective interventions against eating and metabolic disorders, particularly in the context of obesity. This study explores the causal role of LPS, as a key relay of microbiota component-induced neuroinflammation in the dysregulation of the reward system following exposure to high-fat diet (HFD). Methods Through a series of behavioural paradigms related to food-reward events and the use of pharmacological agents targeting the dopamine circuit, we investigated the mechanisms associated with the development of reward dysregulation during HFD-feeding in male mice. A Toll-like receptor 4 (TLR4) full knockout model and intraventricular lipopolysaccharide (LPS) diffusion at low doses, which mimics the obesity-associated neuroinflammatory phenotype, were used to investigate the causal roles of gut microbiota-derived components in neuroinflammation and reward dysregulation. Results Our study revealed that short term exposure to HFD (24 h) tended to affect food-seeking behaviour, and this effect became significant after 1 week of HFD. Moreover, we found that deletion of TLR4 induced a partial protection against HFD-induced neuroinflammation and reward dysregulation. Finally, chronic brain diffusion of LPS recapitulated, at least in part, HFD-induced molecular and behavioural dysfunctions within the reward system. Conclusions These findings highlight a link between the neuroinflammatory processes triggered by the gut microbiota components LPS and the dysregulation of the reward system during HFD-induced obesity through the TLR4 pathway, thus paving the way for future therapeutic approaches. Graphical abstract